FUNGSI BERNILAI VEKTOR - WANDI, SU (2302-0792, 2013)
The definition of function f is a role that relates between x ofone items and single value f(x) of others items. It can be a realscalar and vector. Scalar function is coming from real countsitems and a couple items or a result of a real count items.However, vector is coming from a real count items and theresult vector items. They are not so different; vector hasdirection and value while the real counts only have value.Vector will be analyzed is to prove vector and differentialtheorem function used to vector in R2.